2006
DOI: 10.1007/s11146-006-6014-5
|View full text |Cite
|
Sign up to set email alerts
|

The Pricing of Property Trust IPOs in Australia

Abstract: Following Brounen and Eichholtz (2002) this paper adds to the international literature investigating the underpricing of REIT initial public offerings (IPOs), with a study into Australian property trusts. This study finds that initial day returns can in part be explained by forecast profit distributions (or dividends) and the market sentiment towards property trusts from the date of the prospectus to the date of listing. There is some support for the “winners curse” explanation of underpricing with evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 35 publications
4
32
0
Order By: Relevance
“…It has been used in Lee et al (1996) to identify more informed investors flocking quickly to better issues. Similarly the LNINSTIT variable used in Dimovski and Brooks (2006) identifies large investor/institutional backing at the outset of the issue. Both these variables are tested to determine if more informed investors as proxied in these two variables are able to identify LPT IPOs that will exceed dividend forecasts.…”
Section: Methodsmentioning
confidence: 99%
“…It has been used in Lee et al (1996) to identify more informed investors flocking quickly to better issues. Similarly the LNINSTIT variable used in Dimovski and Brooks (2006) identifies large investor/institutional backing at the outset of the issue. Both these variables are tested to determine if more informed investors as proxied in these two variables are able to identify LPT IPOs that will exceed dividend forecasts.…”
Section: Methodsmentioning
confidence: 99%
“…One of the first reported studies was by Wang, Chan and Gau (1992) In Australia, Dimovski and Brooks (2006) examined 37 property trust IPOs during 1994 to 1999 to report an average underpricing of 1.2%. As with Ling and Ryngaert (1997), they found that underpricing is partly explained by the existence of initial large or institutional investors.…”
Section: Underpricing Cost Literaturementioning
confidence: 99%
“…Dimovski and Brooks (2006) report that LPT IPOs have significant institutional and public equity capital investment support in Australia. They identify that 37 such IPOs raised around $7 billion of equity capital during 1994 to 1999.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an IPO industry sector, Dimovski and Brooks (2005a) report that it was Australia s second largest industry sector in terms of public equity capital raised during 1994 to 1999 and second only because of the Australian Government s partial sale of Telstra. Excluding the Telstra float, property trust IPOs raised twice the public equity capital of any single industry sector and more than twice the equity raised by mining and resources IPOs.…”
Section: Introductionmentioning
confidence: 99%